Robot Imitation: Body Schema and Body Percept - C. A. Acosta-Calderon; H. Hu (Applied Bionics and Biomechanics)
There are two functional elements used by humans to understand and perform actions. These elements are: the body schema and the body percept. The first one is a representation of the body that contains information of the body's capabilities. The second one is a snapshot of the body and its relation with the environment at a given instant. These elements interact in order to generate, among other abilities, the ability to imitate. This paper presents an approach to robot imitation based on these two functional elements. Our approach is gradually expanded throughout three developmental stages used by humans to refine imitation. Experimental results are presented to support the feasibility of the proposed approach at the current stage for 2D movements and simple manipulation actions.